Designing a robot-assisted therapy for individuals with anxiety traits and states - Ab. Aziz, Azizi; Ahmad, Faudziah; Yusoff, Nooraini; Ahmad, Farzana Kabir; Mohd Yusof, Shahrul Azmi (2015)
The recent trend towards developing a new generation of robots capable of operating in human-centered environments, and participating in and assisting our daily lives has introduced the need for robotic systems capable to communicate and to react to their users in a social and engaging way.This type of robot could play essential roles to help individuals with severe cognitive problems.In this paper, several core components to design a robotic assisted therapy to support individuals with anxiety traits and states are presented.